Gratitude and resilience among muslim students in Indonesia - Umriana, Anila; Sugiharto, Dwi Yuwono Puji; Mulawarman; Mahfud, Ashari (Jurnal Ilmu Dakwah, 2025)
Purpose – This study aims to determine the level of gratitude and resilience among students;  to examine the effect of gratitude on the resilience of students at State Islamic Universities in Indonesia Method – This study is quantitative. The number of respondents was 571 from 18 PTKIN in Indonesia. The resilience scale used the Adult Personal Resilience Scale (APRS-20), and the gratitude scale used the Islamic Gratitude Scale (IGS-10). The construct validity and reliability tests used Confirmatory Factor Analysis (CFA). Resilience and gratitude levels were analyzed using descriptive statistics, while the effect test used simple linear regression analysis with the Jamovi application. Result  -  The results of the study show that student gratitude is in the very high category (67.78%), and resilience is in the high category (60.07%). Gratitude has a positive and significant effect on student resilience. The higher the level of student gratitude, the higher the level of resilience. The coefficient of determination (R² = 0.295) indicates that gratitude accounts for 29.5% of the variance in resilience, while the remaining 70.5% is attributed to other factors beyond the scope of this study. Implication – reinforces previous theories and findings that gratitude is closely related to psychological well-being and resilience; universities can develop gratitude-based guidance and counseling programs to improve student resilience; the campus community can create a culture of gratitude that encourages students to be more optimistic, supportive of one another, and able to face difficulties with a positive attitude. Originality/Value – This study is novel in terms of its respondent coverage, comprising PTKIN students from 18 universities in Indonesia. *** Tujuan – Penelitian ini bertujuan untuk menentukan tingkat rasa syukur dan resiliensi di kalangan mahasiswa;  untuk menganalisis pengaruh rasa syukur terhadap ketahanan mahasiswa di Perguruan Tinggi Islam Negeri (PTKIN) di Indonesia Metode – Penelitian ini bersifat kuantitatif. Jumlah responden sebanyak 571 orang dari 18 PTKIN di Indonesia. Skala ketahanan menggunakan Adult Personal Resilience Scale (APRS-20), sedangkan skala rasa syukur menggunakan Islamic Gratitude Scale (IGS-10). Uji validitas konstruk dan reliabilitas menggunakan Analisis Faktor Konfirmatory (CFA). Tingkat ketahanan dan rasa syukur dianalisis menggunakan statistik deskriptif, sedangkan uji pengaruh menggunakan analisis regresi linier sederhana dengan aplikasi Jamovi. Hasil - Hasil penelitian menunjukkan bahwa tingkat rasa syukur mahasiswa berada pada kategori sangat tinggi (67,78%), sedangkan tingkat ketahanan berada pada kategori tinggi (60,07%). Rasa syukur memiliki efek positif dan signifikan terhadap ketahanan mahasiswa. Semakin tinggi tingkat rasa syukur mahasiswa, semakin tinggi pula tingkat ketahanan mereka. Koefisien determinasi (R² = 0,295) menunjukkan bahwa rasa syukur menjelaskan 29,5% varians dalam ketahanan, sementara 70,5% sisanya disebabkan oleh faktor lain di luar lingkup penelitian ini. Implikasi – memperkuat teori dan temuan sebelumnya bahwa rasa syukur erat kaitannya dengan kesejahteraan psikologis dan ketahanan; perguruan tinggi dapat mengembangkan program bimbingan dan konseling berbasis rasa syukur untuk meningkatkan ketahanan mahasiswa; komunitas kampus dapat menciptakan budaya rasa syukur yang mendorong mahasiswa untuk lebih optimis, saling mendukung, dan mampu menghadapi kesulitan dengan sikap positif. Orisinalitas/Nilai – Studi ini bersifat inovatif dalam hal cakupan respondennya, yang meliputi mahasiswa PTKIN dari 18 universitas di Indonesia.